Stress and vibration analysis of interference-fitted tubular joints by finite element analysis - Tan, Kok Hien (Nanyang Technological University, 2023)
A compound cylinder is a type of cylindrical structure that consists of multiple cylinders assembled together by interference fit. Compound cylinders are commonly used in various engineering applications such as pressure vessels, hydraulic cylinders, and pneumatic cylinders. This final year project (FYP) deals with the stress and vibration analysis of large compound cylinders commonly used in industries. The effects of interference fit on the stress distribution, natural frequencies and mode shapes are studied. The student version of ANSYS Mechanical workbench software is used for the finite element analysis presented in this report. As a verification of finite element results for interference fit, certain cases have been compared with theoretical results given by analytical formulae. The results are found to be in close agreement. It is observed from the static structural analysis that the maximum hoop stress of the compound cylinder occurs at the mean radius. The effect of changing the mean radius (keeping the inner and outer radii same) has been studied. When the mean radius is shifted towards inner radius (i.e., inner cylinder becomes thinner and outer cylinder becomes thicker), the maximum permissible interference (limited by yield strength of the material) becomes smaller. From the vibration analysis, it is discovered that only torsional mode frequency is affected by the interference in the absence of friction at the interface. When friction is present, the frequencies of all the modes are not affected by the interference and hence the natural frequencies remain constant. However, it is noticed that as the mean radius is decreased, the torsional mode frequency of inner cylinder for fixed-fixed boundary condition approaches 0 Hz. In comparison to the fixed-free boundary condition of the compound cylinder, the natural frequencies for fixed-fixed boundary condition are significantly higher.